Joanna Sondel-Cedarmas, Nacjonalizm włoski. Geneza i ewolucja doktryny politycznej (1896-1923), 2013 - Zmierczak, Maria (Czasopismo Prawno-Historyczne, 2013)
Joanna Sondel-Cedarmas, Nacjonalizm włoski. Geneza i ewolucja doktryny politycznej (1896-1923), 2013